Perbedaan Pengetahuan Pada Pelayanan Fitofarmaka dengan Sistem Informasi Oleh Tenaga Kefarmasian di Kota Semarang - Sri Suwarni (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2026)
One of the forms of natural medicine in Indonesia is phytopharmaca. Until now, based on the data, there is an increase in the production of phytopharmaceutical preparations. The use of phytopharmaca must continue to be increased for the utilization of Indonesian Herbal medicine. There is an Information System that contains information about Phytopharmacia called SIFITA to support the provision of information by pharmaceutical personnel for patient education. The aim of the study was to determine the success of Phytopharmaca Information System support on the knowledge of Pharmaceutical Workers in Semarang City. Prospective quantitative research design. The sample used was 350 pharmaceutical workers in Semarang City who work in health care facilities. The instrument was a valid and reliable questionnaire. The instrument question constructs used the HOT-Fit (Human Organization Technology, Net benefit) method for SIFITA and measurement of success in improving knowledge. The analysis used Chi Square test, Spearman's Rank Correlation Coefficient test, and N-Gain test. The results of this study p value = 0.00 0.05 means that there is a difference in knowledge before and after using the Phytopharmaceutical Information System by Pharmaceutical Workers in Semarang City, p value = 0.00 0.05 means that there is an influence of the Phytopharmaceutical Information System on the knowledge of Pharmaceutical Workers in Semarang City with a moderate relationship strength level of 0.59, and this Phytopharmaceutical Information System measured by NGain is quite effective 69.77%.